Promoting STEM (Science, Technology, Engineering, and Mathematics) for Young Learners of Indonesia - Lailisna, Novi Nur; Muhamad Ansori (JEET, Journal of English Education and Technology, 2024)
This paper describes youth as the next generation of Indonesia who must be understood and inspired for their subsequent learning and career STEM (Science, Technology, Engineering, and Mathematics) based. STEM discipline is commonly an inconvenient subject for youth, especially young learners. Collecting research papers that prove STEM had positively supported youth for their learning and career, this paper will recommend young learners become inspiring and produce a product in the future. Generally, it explores new trends overseas that Indonesia also has a chance for needed-promoted youth’s skills for further education